A Literary Study Of Samanya Vishesh Siddhanta In The Management Of Amlapitta - Bishnoi, Mukul Pratap; Baronia, Chandrashri; Mishra, Anshuman (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is a comprehensive discipline that values knowledge of every aspect in order to live a healthy,prosperous, and happy life. This wealth can be found in the form of its fundamental concepts. Thefundamental principles of this discipline are like deep tree roots that will always securely hold the massiveAyurvedic tree. Similarity or uniformity is represented by Samanya, whereas dissimilarity or non-uniformity is represented by Vishesh. Every disease is caused by a disruption in the state of balance of thebody’s dosha, dhatu, or mala, i.e., a rise or reduction in their state. The disturbance of Agni causesAmlapitta (hyperacidity), which disrupts the normality of the pitta dosha. Many people are suffering fromdigestive issues as a result of changes in their diet and lifestyle. Amlapitta’s condition in one of them. Thecore idea of SamanyaVishesh Siddhanta can be used to cure this. The idea and relevance of SamayaVishesh Siddhant in curing. The essential premise in the treatment of any ailment is Samanya VisheshSiddhanta. This holy concept given forth by our Acharya s may not only be used to heal Amlapitta, butalso to prevent it from recurring.